2022
DOI: 10.17358/brcs.3.1.74
|View full text |Cite
|
Sign up to set email alerts
|

The Mediation Role of Job Satisfaction and Organizational Commitment In The Relationship Between Person-Organization Fit (P-O Fit) and Employee Performance

Abstract: This study aims to empirically prove the relationship between person-organization (P-O-Fit) on employee performance with job satisfaction and organizational commitment as mediating variables. The importance of conducting research to deepen the understanding of Person-Organization Fit and job performance both directly and indirectly, in this case, mediating job satisfaction and organization commitment, which leads to the overall employee job performance and indisputably on increasing performance productivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…JS is also used as an intervening variable, due to the need to re-establish its mediation levels. This was supported by (Prasetyaningrum & Hendarsjah, 2022), where POF indirectly influenced EP through JS. However, (Farooqui & Nagendra, 2014) stated that POF did not influence EP through the mediation of JS.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…JS is also used as an intervening variable, due to the need to re-establish its mediation levels. This was supported by (Prasetyaningrum & Hendarsjah, 2022), where POF indirectly influenced EP through JS. However, (Farooqui & Nagendra, 2014) stated that POF did not influence EP through the mediation of JS.…”
Section: Introductionmentioning
confidence: 68%
“…Based on previous studies, such as (Farooqui & Nagendra, 2014;Hamstra, Van Vianen, & Koen, 2019;Sørlie, Hetland, Bakker, Espevik, & Olsen, 2022) POF also influenced EP. Moreover, (Prasetyaningrum & Hendarsjah, 2022;Rifqi & Ningsih, 2022;Yeni, Situngkir, Amin, & Edward, 2022) did not determine any influence of POF on EP. Since differences are observed from these previous reports, subsequent analyses are expected to prove the influence of POF on performance.…”
Section: Introductionmentioning
confidence: 84%
“…The results of this study are corroborated by research conducted by Suwandana & Perdanawati. (2020) and Prasetyaningrum & Hendarsjah. (2022) which found that there was a significant positive effect on job satisfaction on employee performance.…”
Section: The Effect Of Job Satisfaction On Employee Performancementioning
confidence: 99%
“…Organisasi dapat meyakinkan kepada karyawannya seperti kesesuaian antara nilai-nilai organisasi dengan nilai-nilai karyawan yaitu Person-Organization Fit (P-O fit). Studi ini menjadi menarik bagi peneliti seperti yang dikemukakan (Prasetyaningrum, T., & Hendarsjah, H. 2022;Saputro, 2021;Fatmasari, 2017;Santoso dan Irwantoro, 2014;Astuti, 2010;r, (1996); (Chatman, 1989); (O'Reilly, 1991).…”
Section: Pendahuluanunclassified